Undernutrition and associated factors among adult HIV/AIDS patients receiving antiretroviral therapy in eastern zone of Tigray, Northern Ethiopia: a cross-sectional study - Gebru, Tsegu Hailu (Arch Public Health, 2020)
BACKGROUND: Undernutrition and HIV/AIDS are highly prevalent in sub-Saharan Africa, Ethiopia inclusive as linked in a vicious cycle. Thus, several studies have documented that undernutrition among HIV/AIDS patients increases the risk of mortality, decrease survival rates, affect the overall clinical outcome and quality of life. Despite this fact, information about the burden of undernutrition and associated factors among adults receiving antiretroviral therapy is lacking in the particular study area. Hence, this study aimed to examine the prevalence of undernutrition and associated factors among adult HIV/AIADS patients receiving antiretroviral therapy patients in Eastern Zone of Tigray, Northern Ethiopia. METHODS: A cross-sectional research design was adopted in data collection while systematic sampling technique was employed to sample and select the study subjects. A structured questionnaire was used to collect information from 394 study subjects through face to face method. Also, data on demographics, laboratory and anthropometric variables were collected from each selected patients sampled. The data collected were entered and analyzed using SPSS version 22.. Bivariate and multivariable logistic regression analysis with 95% confidence interval were used to find factors associated with undernutrition. The adjusted odds ratio was calculated to show the strength of the association. Variables with p-value of < 0.05 were considered statically significant. RESULTS: The mean age of the respondents was 41 (± 10). Out of 394 study respondents, about 42.9% of them were undernourished (95% CI: 37.8–47.7). Respondents who had CD4+ count less than 200 cells/μl (AOR = 1.84; 95% CI: 1–3.36), being advanced clinical staging (AOR = 3.6; 95% CI: 2.11–6.18), and not taking co-trimoxazole preventive therapy (AOR = 2.38; 95% CI: 1.21–4.6) were independently associated with undernutrition. CONCLUSION: The result of this study indicated that the prevalence of undernutrition was high. Respondents with advanced clinical stage of CD4+ count less than 200 cells/ul and those that were not taking co-trimoxazole preventive therapy was found to be positively associated with undernutrition. Therefore, the implementation of nutritional programs is very crucial to improve the nutritional status of HIV/AIDS patients in the particular study.